Life is unfair, and so are racing sports: some athletes can randomly benefit from alerting effects due to inconsistent starting procedures - Dalmaijer, Edwin S.; Nijenhuis, Beorn G.; Van der Stigchel, Stefan (Frontiers in Psychology, 2015)
The Olympics are the world's largest sporting events, attracting billions of viewers worldwide. Important parts are racing sports, such as running, swimming and speed skating. In these sports, athletes compete against each other in different heats to determine who wins the gold, or who is granted a place in the final. Of course, the gold goes to whoever is the most talented and has trained the hardest. Or does it? Here we argue that subtle differences between athletes' starts can bias the competition, and demonstrate this in the results of speed skating at the 2010 Winter Olympics. This bias could be removed by simple alterations to current starting procedures. The proposed change would greatly improve racing sport fairness, which currently suffers from an injustice that disadvantages not only athletes, but entire nations rooting for them.